HEALTH SERVICES UTILIZATION AMONG CHINESE AMERICAN OLDER ADULTS: THE ROLE OF SOCIAL SUPPORT. (11th November 2018) - Wang, J; Kong, D; Sun, B; Dong, X
Abstract: Older Chinese Americans (≥65 years) have a distinct social support profile and greater health care service utilization than their Caucasian counterparts. To date, it is unknown if the unique social support profile in older Chinese Americans is related to their use of health service utilization. Using the Andersen Behavioral Model of health services use as the conceptual framework of this study, we examined the relationship of social support from spouse, family, and friends with hospitalizations and emergency department (ED) visits among older Chinese Americans, with a focus on potential moderation effects between social support and need factors of health service use (i.e., medical illnesses and physical function). This study utilized data from the Population Study of Chinese Elderly (07/2011-07/2013; N=3, 157), the largest population-based study on psychosocial well-being of Chinese older adults in Western countries. In logistic regression analyses, main effects of social support were not related to hospitalization or ER visits, after adjusting for demographic, clinical, and functional covariates. Significant interaction between social support from spouse and the number of limitations in (instrumental) activities of daily living was related to lower risk of hospitalization (Odds Ratio [OR]=0.98 [0.96–0.99], p<0.05) and ED visits (OR=0.97 [0.95–0.99], p<0.01). This finding suggests that among older Chinese American adults with functional limitations, more social support from spouse was related to lower odds of hospitalizations and ED visits. Future studies should comprehensively measure social support (e.g., content, amount) and investigate how unnecessary acute health service utilization in this population may be reduced by social support interventions.